Teaching Literature, Teaching Values, and Advancing SDG 4: A Case Study of UNESCO Core Values in an Indonesian Islamic University - Masulah Masulah; Fabiola Dharmawanti Kurnia; Ali Mustofa (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To investigate lecturers’ and students’ views of UNESCO core values in literature teaching and to examine how these values are manifested in literary learning at a Muhammadiyah University in East Java, Indonesia. Method: Employing a qualitative case study design involving three literature lecturers and thirty-one undergraduate students. Data were collected through questionnaires, semi-structured interviews, classroom observations, literary analysis activities, field notes, and document analysis. Results: The findings show that both lecturers and students strongly support the integration of UNESCO core values into literature teaching. Among the eight UNESCO core values, religiosity emerged as the most dominant value, reflecting the institutional philosophy of Muhammadiyah education. The values were integrated through literary analysis, classroom interaction, teaching materials, and lecturers’ role modeling. Literature classrooms also promoted empathy, tolerance, responsibility, compassion, and social awareness while maintaining literary appreciation and critical inquiry. Novelty: Offering a novel contribution by examining the integration of UNESCO Core Values into literature teaching within an Indonesian Islamic higher education context, demonstrating how literature can function as a vehicle for values-based education while advancing Sustainable Development Goal 4 (Quality Education), particularly Target 4.7, which emphasizes education for sustainable development, global citizenship, cultural diversity, and the promotion of peace and human values. The findings extend the discourse on holistic education by illustrating how literary learning fosters students’ literary competence, ethical awareness, character development, and social responsibility within a faith-based university setting.